(Auto)refleksyjność w Tremie Alfreda Hitchcocka. O adaptacji powieści Selwyna Jepsona - Birkholc, Robert (Załącznik Kulturoznawczy, 2020)
The article is devoted to self-reflexive strategies used in Stage Fright by Alfred Hitchcock, based on a novel Man Running by Selwyn Jepson. Unlike European modernists such as Jean-Luc Godard, Hitchcock didn’t use experimental film form, but he applied some metafictional narrative techniques within a classical narrative structure. Comparing Stage Fright with the literary original, the author shows how Hitchcock made his film self-referential. The director achieved it by embedding the action deeper in a theater environment, adding a complex symbol of a curtain, using a figure of authorial metalepsis, problematizing the issue of the characters, identity and making narration unreliable. Stage Fright is self-reflexive not only on the level of the plot and dialogues, but also on the level of the narration. As the author argues, Hitchcock not only talks about the mechanisms of creating the spectacle, but also draws attention to the role of lies, fiction and play in our lives.